2021
DOI: 10.4103/ua.ua_112_20
|View full text |Cite
|
Sign up to set email alerts
|

The use of preoperative neutrophil–lymphocyte ratio and lymphocyte–monocyte ratio in predicting survival and groin node involvement of patients with squamous cell carcinoma of penis

Abstract: Introduction: The association between inflammation and malignancies is being recognized. In this study, we assessed the use of preoperative neutrophil–lymphocyte ratio (NLR) and lymphocyte–monocyte ratio (LMR) in predicting cancer-specific survival (CSS) and inguinal node involvement in patients with carcinoma penis. Methods: Sixty-nine patients operated for squamous cell carcinoma penis with inguinal node dissection between 2012 and 2020 were identified. We recorded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…After the primary screening process, fourteen studies were further evaluated in full text. The final analysis included seven articles [ 7 , [9] , [10] , [11] , [12] , 16 , 17 ] for the systematic review, six of which [ 7 , [9] , [10] , [11] , [12] , 16 ] were eligible to be included in the meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the primary screening process, fourteen studies were further evaluated in full text. The final analysis included seven articles [ 7 , [9] , [10] , [11] , [12] , 16 , 17 ] for the systematic review, six of which [ 7 , [9] , [10] , [11] , [12] , 16 ] were eligible to be included in the meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the median CSS was also not described in the results of most of the studies. However, Chen Hu et al [ 12 ] and Jindal et al [ 7 ] reported that the penile cancer patients in their cohort had a median CSS of 33 months and 18 months, respectively. The value of NLR was obtained from a complete blood count examination taken from peripheral blood samples prior to the surgical procedure which the course varied from 1 month to 3 days before inguinal lymph node dissection surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated NLR was significantly correlated with worse OS and PFS, but only by conducting a univariate analysis [ 68 ]. Jindal et al reported concordant results regarding the association between NLR and pN+ disease and survival outcomes [ 69 ]. Li et al investigated the prognostic significance of NLR in 228 patients treated with bilateral ILND for PSCC.…”
Section: Systemic Inflammation Markers In Penile Cancermentioning
confidence: 99%